EUROPE AND THE ARAB SPRING: TWO CASE STUDIES - Daniel Gugan (European Scientific Journal, ESJ, 2013)
This study will portray an assessment of the Euro-Mediterranean relations from a unique perspective: two countries from the MENA84 region will be examined through the lenses of Europe, with which we will try to develop a fair evaluation of the EU's role in the Arab Spring. The main goal will be to gain insight into the EU's foreign policy making through the close examination of the European Neighborhood Policy85 (ENP), which plays a key role in the EU's reactions to the Arab uprisings. The ENP's core documents (Action Plans and Progress Reports) will be examined to discover the EU's policy agendas regarding the MENA region and especially the two case study countries.